Competition, Systemic Risk and Financial Inclusion: Assessing the Adequacy of South Africa’s Merger Control Framework for Navigating Policy Frictions Arising in the FinTech Industry - Stathoulis, Maria Olga (University of the Witwatersrand, Johannesburg, 2023)
An adequacy assessment is conducted through outlining a proposed FinTech competition policy that serves as a yardstick in relation to which the merger control framework is evaluated. The adequacy assessment is informed by whether the merger control framework, in theory, facilitates the implementation of the proposed policy principles that are calculated to aid competition authorities to balance competition, systemic risk, and data protection concerns in a manner that optimises financial inclusion. This research report proposes that the balancing exercise built into the merger control framework, the substantial public-interest grounds that factor in industry-specific policies, and the socio-economic framework within which the public-interest provisions should be considered, will enable the competition authorities to navigate policy frictions arising in the FinTech industry. However, the Minister of Finance’s power to exclude bank mergers from the purview of the merger control framework and the Prudential Authority’s stability-orientated primary objectives, have the potential to undermine competition in the banking sector. Competence and resource constraints aside, regulatory authorities can only be as effective as their mandate is appropriate. To create an appropriate regulatory architecture and optimal jurisdiction allocation, reform permutations that redefine the relationship between the Banks Act 94 of 1990 and the Competition Act 89 of 1998 are suggested. Merger control is as much of a transaction-specific analysis as it is context specific. Therefore, a FinTech-traditional financial market inquiry is recommended to enable the competition authorities and, more broadly, the Intergovernmental Fintech Working Group members, to understand the current state, and trajectory, of the FinTech industry
A research report Submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report School of Law, University of the Witwatersrand, Johannesburg 2023
Keywords: FinTech; Competition Commission; Minister of Finance; Prudential Authority; Competition; Exclude bank mergers; InterestFinTech competition policy; UCTD; SDG-8: Decent work and economic growth